A Stacked Microstrip Antenna Array with Fractal Patches - Xueyao Ren; Xing Chen; Yufeng Liu; Wei Jin; Kama Huang (International Journal of Antennas and Propagation)
A novel microstrip antenna array, which utilizes Giuseppe Peano fractal shaped patches as its radiation elements and adopts a two-layer stacked structure for achieving both wideband and high-gain properties, is proposed. Parametric study estimates that the proposed antenna’s size can be arbitrarily adjusted by changing the fractal proportion while high aperture efficiency is maintained. Two prototypes with 2 × 2 and 4 × 4 fractal patches, respectively, on each layer are designed, fabricated, and measured. Both simulation and measurement results demonstrate that the proposed antenna possesses encouraging performances of wideband, high directivity, and high aperture efficiency simultaneously; for example, for the two prototypes, their S11<-10 dB impedance bandwidths are 23.49% and 18.49%, respectively; at the working frequency of 5.8 GHz, their directivities are 12.2 dBi and 18.2 dBi, and their corresponding aperture efficiencies are up to 91.0% and 90.5%, respectively.